Cognitive Analysis Using Rasch Modeling As an Assessment for Physical Fitness Knowledge for College Students - Didin Budiman; Ricky Wibowo (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
Having good physical fitness is the foundation for carrying out daily activities. Maintaining physical fitness requires knowledge and understanding for performing meaningful physical activities. This study aimed to analyze the physical fitness knowledge test instrument for college students using the Rasch modelling data analysis technique. The design, development, and research method employed the product model and research tool that consisted of four stages, including analysis, design, development, and evaluation. The samples involved in the instrument trial were 67 students from one university in Indonesia. The analysis used was the content validity ratio for testing content validity and the item response theory/Rasch model test employing Winstep software to determine the validity and reliability of the test instrument. The results of the data analysis showed a match between the students and the test instruments with very good quality items. It concludes that the test instrument development using the Rasch model can detect student misconceptions on physical fitness knowledge material.